Sub-National Institutional Contingencies, Network Positions, and IJV Partner Selection - Shi, W.; Sun, S.; Peng, Mike (Blackwell Publishing Ltd, 2012)
The differences in sub-national institutions within large and complex emerging economies have been increasingly noted. Drawing on social network theory and the institution-based view, we argue that two network structural attributes of domestic firms - centrality and structural holes - have distinctive values in different sub-national regions where institutional contexts differ widely. In addition, these sub-national institutional contingencies influence the attractiveness of different network attributes to foreign entrants seeking international joint venture (IJV) partners. Specifically, in regions where the degree of marketization is high, centrally positioned domestic firms are more likely to be selected by foreign entrants as IJV partners. In regions where the degree of marketization is low, domestic broker firms are more attractive IJV partners. Results from the electrical and information technology industries in 18 provinces in China largely support our hypotheses.